2009
DOI: 10.1098/rspb.2009.0640
|View full text |Cite
|
Sign up to set email alerts
|

A potent effect of observational learning on chimpanzee tool construction

Abstract: Although tool use occurs in diverse species, its complexity may mark an important distinction between humans and other animals. Chimpanzee tool use has many similarities to that seen in humans, yet evidence of the cumulatively complex and constructive technologies common in human populations remains absent in free-ranging chimpanzees. Here we provide the first evidence that chimpanzees have a latent capacity to socially learn to construct a composite tool. Fifty chimpanzees were assigned to one of five demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 39 publications
6
86
1
1
Order By: Relevance
“…Importantly, Price et al (2009) obtained these results in the scenario where the chimpanzees learned from one conspecific, not from a majority. A similar finding was reported by Whiten (1998): in this study, chimpanzees preferentially used their first-learned action pattern that had been demonstrated to them by one human experimenter, even after discovering that other sequences worked equally well (Whiten, 1998).…”
Section: Do Primates Show Conformity?supporting
confidence: 52%
See 1 more Smart Citation
“…Importantly, Price et al (2009) obtained these results in the scenario where the chimpanzees learned from one conspecific, not from a majority. A similar finding was reported by Whiten (1998): in this study, chimpanzees preferentially used their first-learned action pattern that had been demonstrated to them by one human experimenter, even after discovering that other sequences worked equally well (Whiten, 1998).…”
Section: Do Primates Show Conformity?supporting
confidence: 52%
“…The second issue that pertains directly to our focus of demarcating social from majority influences is related to the finding that chimpanzees who have acquired their behaviour socially have been shown to be relatively rigid in the use thereof, even at the cost of efficiency (Price, Lambeth, Schapiro, & Whiten, 2009). Importantly, Price et al (2009) obtained these results in the scenario where the chimpanzees learned from one conspecific, not from a majority.…”
Section: Do Primates Show Conformity?mentioning
confidence: 99%
“…The apparent conservatism exhibited by chimpanzees within studies of social learning may provide an intriguing insight. Chimpanzees appear to show a striking tendency to perseverate with learned responses, often in the face of exposure to, or even experience of, more effective alternatives (Marshall-Pescini & Whiten, 2008;Hrubesch, Preuschoft, & van Schaik, 2009;Price et al, 2009;Hanus, Mendes, Tennie, & Call, 2011;Hopper et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The remarkable copying by chimpanzees has also been shown to allow introduced behavioral variants to spread through social groups under more naturalistic conditions, creating captive behavioral traditions Whiten et al, 2007). Perhaps even more strikingly, it has also been shown that the power of these social influences is such that chimpanzees will continue to use socially learned behaviors, even when they are redundant (Price, Lambeth, Schapiro, & Whiten, 2009), or when the learned behavior causes them to go against personal preferences (Hopper, Schapiro, Lambeth, & Brosnan, 2011). Consequently, it appears that, whatever the mechanism involved, for these tasks, chimpanzees seem capable of the sort of high fidelity transmission proposed by Tennie et al (2009) to be vital for cumulative culture.…”
Section: High Fidelity Behavioral Transmission In Chimpanzeesmentioning
confidence: 99%
“…For example, there is an important distinction between manufacture and innovation. When tool makers make a new tool having first seen a suitable example of the tool itself [5,6], or of the tool being used by conspecifics [21,22], they have a template tool-shape to work towards. Assuming that they recognize that the example tool is a suitable tool to solve the task they face (a difficult task in itself, but helped if they have used it themselves or seen others do so), their task is to transform the available materials so that they resemble the example tool.…”
Section: Introductionmentioning
confidence: 99%